2013
DOI: 10.1016/j.compfluid.2012.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Efficient GPU implementation of a two waves TVD-WAF method for the two-dimensional one layer shallow water system on structured meshes

Abstract: The numerical solutions of Shallow Water Equations are useful for applications related to geophysical flows that usually take place in large computational domains and could require real time calculation. Therefore, parallel versions of accurate and efficient numerical solvers for high performance platforms are needed to be able to deal with these simulation scenarios in reasonable times. In this paper we present an efficient CUDA implementation of a first and second order HLL methods and a two-waves TVD-WAF on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 30 publications
0
57
0
1
Order By: Relevance
“…GPU acceleration has been applied to tsunami models in the past, although primarily on grids with fixed spatial resolution, including those of Acuña and Aoki (), Lastra et al (), De La Asunción et al (), Brodtkorb et al (), de la Asunción et al (), Smith and Liang (), Amouzgar et al (), and De La Asunción et al (). A recent application to an AMR code is presented by de la Asunción and Castro () for a landslide‐generated tsunami, and GPU acceleration of other AMR algorithms have been pursued in other communities, particularly in astrophysics (e.g., Schive et al, ; Wang et al, ).…”
Section: Related Work and Other Approachesmentioning
confidence: 99%
“…GPU acceleration has been applied to tsunami models in the past, although primarily on grids with fixed spatial resolution, including those of Acuña and Aoki (), Lastra et al (), De La Asunción et al (), Brodtkorb et al (), de la Asunción et al (), Smith and Liang (), Amouzgar et al (), and De La Asunción et al (). A recent application to an AMR code is presented by de la Asunción and Castro () for a landslide‐generated tsunami, and GPU acceleration of other AMR algorithms have been pursued in other communities, particularly in astrophysics (e.g., Schive et al, ; Wang et al, ).…”
Section: Related Work and Other Approachesmentioning
confidence: 99%
“…Here, only structured grids on ( x , y ) or ( θ , φ ) plane are considered. We use the HLLC scheme written as a PVM method . We use the three stages TVD RK method that is also third‐order accurate in time.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Subsequently a Roe scheme was presented by de la Asunción et al (2011), a first order accurate, finite difference model is adopted by Kalyanapu et al (2011) andLamb et al (2009) developed a diffusion wave model, based on CUDA programming language. More recently, several attempts to develop numerical schemes with high order of accuracy have been proposed de la Asunción et al, 2013) also adopting unstructured mesh de la Asunción et al, 2013). Simulations of practical test cases have been reported by de la Asunción et al (2013); Brodtkorb et al (2012) which showed relevant speed-ups (in comparison with nonparallel codes) for dam-break waves.…”
Section: Introductionmentioning
confidence: 97%
“…More recently, several attempts to develop numerical schemes with high order of accuracy have been proposed de la Asunción et al, 2013) also adopting unstructured mesh de la Asunción et al, 2013). Simulations of practical test cases have been reported by de la Asunción et al (2013); Brodtkorb et al (2012) which showed relevant speed-ups (in comparison with nonparallel codes) for dam-break waves. Moreover, attempts to use multiple GPUs to tackle larger simulations have been presented .…”
Section: Introductionmentioning
confidence: 97%